Obesity: A Multi Perspective of Physiology and Neurobiology Energy Regulation - Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Indonesian Biomedical Journal, 2024)
BACKGROUND: World Health Organization has reported four million people die every year due to obesity comorbidity, and the prevalence of obesity is keep increasing, especially after COVID-19. Obesity has been defined as a chronic disease involving adipose tissue dysfunction which leads to metabolic diseases and psychosocial consequences. The review article will highlight some recent researches regarding the new conceptual framework that integrates both metabolic drives, as well as to summarize the numerous discussions about the current understanding of hypothalamic control of food intake and energy homeostasis.CONTENT: Obesity apparently is not simply regulated only by food and exercise. Hypothalamus takes part in controlling energy intake and expenditure via appetite regulation. Hedonic control in cortical and subcortical brain areas process cognitive, reward, information, and executive function. Managing metabolic adaptation, browning the white adipose tissue, and preserving lean mass can be another strategy to safely manage obesity.SUMMARY: Obesity need to be managed in a multimodal strategy including neurophysiology and physiology approach, together with environment support. Thus, a weight regain can be prevented. Commitment from both scientific and regulation point of view can shed a light to eradicate obesity.KEYWORDS: adipocyte, appetite, nutrition, obesity, physical activity, reward, satiety